Empowering the public-private partnership. The future of America's local government - Voinovich, George V. (Ohio University Press, 2017)
America's urban centers face many challenges, from decaying infrastructure to declining population and a falling tax base. At the same time, there is increasing interest in cities as sites of renewal and economic opportunity. How can city leaders facing financial constraints harness this positive energy in a sustainable way? The story of Cleveland in the early 1980s is a valuable example of how city governments can partner with private entities - businesses, nonprofits, unions, and others - to drive growth and preserve quality of life in urban centers. In the early 1980s, under the leadership of Mayor George V. Voinovich, Cleveland went from financial default to being named "American's Comeback City." This turnaround happened in only a few years, and it's something from which Cleveland still benefits. In fact, the public-private partnership, or P3, model that Voinovich pioneered, has since become the gold standard for cities seeking to maximize resources. Before his death in June 2016, Voinovich developed this handbook, a how-to manual that not only explains the technical aspects of creating these partnerships but also describes in depth how the private sector can be a powerful agent to improve the operations of local government. It outlines the organization of the Cleveland public-private alliance; the motivations of those who gave of their time, talent, and money; and how city officials and their partners monitored implementation of the strategic plan